GAMBARAN KETERSEDIAAN PANGAN, KECUKUPAN ENERGI PROTEIN DAN STATUS GIZI PADA BALITA (12-59 BULAN) DI PENGUNGSIAN GUNUNG SINABUNG TAHUN 2016 - Dika Saraswati; Fitri Ardiani; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Children under five years are particularly vulnerable to problems of nutrition for children under five years require more nutrients. Natural disasters can threaten and interfere with people's lives like the eruption of Mount Sinabung which made them to flee so as to make people live within the limitations of the limited availability of food, for example. This causes stunted growth and development in infants that will affect physical endurance and intelligence so that it can have an impact on life in the future. This study aims to describe the availability of food, the number of energy and protein adequacy and nutritional status of infants in evacuation Sinabung. This research was a descriptive cross sectional design. Samples taken are entire populations that as many as 95 children under the age of 12-59 months. Data collected include food availability, energy consumption and protein, as well as nutritional status was analyzed by univariate to see the frequency distribution. The results showed that most of the nutritional status of children under five by BB / U in the category of less than 58,9%, TB / U in the category amounted to 65.2%, and weight / height within the normal ranges of 62.2%. Of 38.9% children who fulfilled the need for energy, and amounted to 75.8% children who fulfilled their protein requirements. The availability of food in the family of children in refugee camps in a state of mild hunger rate of 80.0% and in a state of famine was 20.0%. Expected their mothers raising awareness on health and nutritional needs are increased in children under five years and a concerted effort from the government to further increase the availability of food while in refugee camps in order to avoid food shortages. Keywords : Food Availability, Energy And Protein Adequacy, Nutritional Status Of Children Under Five Years